Replacement for a preoccupied Docosia Winnertz (Diptera: Mycetophilidae) name - Kurina, Olavi; Ševčík, Jan (Zootaxa, 2013)
In our recent paper on Palaearctic Docosia Winnertz, 1863, a new species was described under the name Docosia turkmenica Kurina & Ševčík, 2012. The material originated from the Kopet Dag Mountains (Big Bakhcha River) in southwest Turkmenistan and was named for its occurrence in the country (Kurina & Ševčík 2012). Unfortunately, the authors were not aware of a previous paper by Zaitzev (2011) describing two new Docosia species from Turkmenistan (Kara Kala) and Russia (Astrakhan). The species described from Turkmenian material—Docosia turkmenica Zaitzev, 2011—was also named to indicate its origin. Consequently two identical species-group names (primary homonyms) were established for different nominal taxa (see also ICZN: Article 57.2). Therefore, for nomenclatural stability, Docosia trispinosa Kurina & Ševčík nom. nov. is proposed herewith for the invalid junior homonym, Docosia turkmenica Kurina & Ševčík. In addition, D. turkmenica Zaitzev, 2011 has been discussed in respect to the key of the Central Asian species by Kurina & Ševčík (2012).